A Question from Series and Sequence.

Asked by  | 14th Sep, 2008, 11:01: PM

Expert Answer:

let first term of G.P. be A and geometric ratio be R

so α = ARp-1

β = ARq-1

γ = ARr-1

α^q-r · β^r-p · γ^p-q = A(q-r+r-p+p-q) R(pq-pr-r+q + qr-pq -r+p+pr-qr - p+q) = A0R0 = 1

now taking log on both sides

(q-r) log α + (r-p) log β + (p-q) log γ = 0.

here we have used the formulas log(a.b.c) = loga + logb +logc

and log an = n loga

Answered by  | 15th Sep, 2008, 01:06: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.